THE SERVICE QUALITY DEVELOPMENT OF BANGKOK ARENA
The objectives in this mixed method research were to study the level of satisfaction, and expectations services of Bangkok Arena, and to study the development of service quality of Bangkok Arena. The respondents in the quantitative phase were 272 Bangkok Arena members, and the in - depth interview was conducted with collected data from 6 people in qualitative phase. The statistics used to analyze the data were percentage, mean, standard deviation, t - test and comparing expectations and satisfaction to find the quality of service and analyze the content Presented in the form of tables and information accompanying the essay. The research results showed that the satisfaction was at a high level ( = 3.54, S.D. = 0.20), and the expectations was at a high level ( = 3.72, S.D. = 0.21). When considering the comparison of expectations and satisfaction It was found that overall, there was a statistically significant difference at the 0.05 level. When considering each aspect comparing expectations and satisfaction, it was found that there were statistically significant differences at the 0.05 level in 5 areas: 1. Information Technology Management 2. Tangibles 3. Responsiveness 4. Advertising and Public Relations 5. Assurance, Empathy and Reliability there was no statistically significant difference at the 0.05 level. The difference between expectations and satisfaction with service quality was found that the services were in lower quality than the expected level. This corresponds to in - depth interviews. The Bangkok Arena must have the standards of the building, and premises. The Bangkok Arena should propose a budget plan for the maintenance of the entire facility system with more variety of activities. There should be a regular staff meeting, training on service mind. There should be publicity about the process of participating in activities, opening time services in all channels, and the use of technology to provide services. , number=1, journal=Academic Journal of Thailand National Sports University, author=Wongsabut, Watcharee and Noriya, Wanchalee and Suksa – Ard, Prasertchai and Rawang - Karn, Nug – Rob, year=2022, month=Dec., pages=29–42